2023
DOI: 10.2174/1570159x20666220302151224
|View full text |Cite
|
Sign up to set email alerts
|

Beyond its Psychiatric Use: The Benefits of Low-dose Lithium Supplementation

Abstract: Lithium is most well-known for its mood stabilizing effects in the treatment of bipolar disorder. Due to its narrow therapeutic window (0.5-1.2 mM serum concentration), there is a stigma associated with lithium treatment and the adverse effects that can occur at therapeutic doses. However, several studies have indicated that doses of lithium under the predetermined therapeutic dose used in bipolar disorder treatment may have beneficial effects not only in the brain but across the body. Currently, literature sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 186 publications
2
15
0
Order By: Relevance
“…Furthermore, we found that mdx -VWRLi mice had greater novel object recognition compared with mdx -VWR mice, suggesting that Li supplementation had an additive effect, which is impressive given that the mdx -VWRLi mice ran significantly less. Thus, we attribute the improvements in spatial memory in the mdx -VWRLi mice largely to Li supplementation, which is consistent with the neuroprotective effects of Li 35,6062 .…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Furthermore, we found that mdx -VWRLi mice had greater novel object recognition compared with mdx -VWR mice, suggesting that Li supplementation had an additive effect, which is impressive given that the mdx -VWRLi mice ran significantly less. Thus, we attribute the improvements in spatial memory in the mdx -VWRLi mice largely to Li supplementation, which is consistent with the neuroprotective effects of Li 35,6062 .…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore and similar to our tideglusib experiments, the mdx -VWRLi mice had the lowest RER compared with the mdx -SED mice, which is indicative of enhanced oxidative fiber expression (Figure S2). Given the fact that oxidative fibers are more insulin sensitive than their glycolytic counterparts 36 and that Li is a well-known insulin mimetic 35 , we next examined the effects of VWR and Li on insulin sensitivity. Insulin tolerance tests show that mdx -SED mice were insulin resistant compared with WT, mdx -VWR, and mdx -VWRLi mice (Figure 2E-F).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Taken together, lithium may reduce neuroinflammationrelated suicidal behavior by inhibiting inflammatory pathways. Second, lithium may also prevent some of the physical comorbidities that lead to premature death [47].…”
Section: Discussionmentioning
confidence: 99%